Fiber optic gyroscope with output signal noise reduction system: effect of system parameters on noise reduction - Spiridonov, Dmitriy Mikhailovich; Vadivasova, Tatjana Evgenevna; Obukhovich, Dmitry Vyacheslav (Известия высших учебных заведений: Прикладная нелинейная динамика, 2025)
The purpose of this work is to determine the optimal parameters for matching the signals of the measuring channels of a fiber-optic gyroscope with an output signal noise reduction system. Methods. The paper analyzes the circuit of a fiber-optic gyroscope with an output signal noise reduction system based on subtracting the signal of the reference measuring channel containing the intensity noise of the optical radiation source from the signal of the main measuring channel containing the useful information signal and the noise component. Four signal matching conditions are defined, failure to meet which can lead to a decrease in the noise suppression efficiency or an increase in the noise level. For each of the conditions under consideration, the parameters of the noise reduction system are determined and mathematical expressions are derived for the dependence of their influence on the level of spectral density of noise in the output signal of the gyroscope, mathematical modeling is carried out in a wide range of variation of the parameters under consideration. To confirm the obtained results, a computer simulation of the operation of a digital fiber-optic gyroscope with a closed feedback loop for measuring angular velocity and an output signal noise reduction system was carried out under conditions of varying the parameters of the noise reduction system. Results. For each parameter under consideration, the shape and degree of influence on the noise level were obtained, and the optimal value of each parameter was determined, at which the minimum value of the spectral density of noise in the output signal was observed. Conclusion. The conducted study confirms the correctness of the derivation of analytical expressions describing the formation of the noise component of the output signal of a fiber-optic gyroscope with a noise reduction system under conditions of incomplete matching of the signals of the main and reference measuring channels. A quantitative assessment of the requirements for the accuracy of this matching was obtained for such parameters as: time matching, matching by signal intensity, by bandwidth and by the state of polarization of optical radiation.